2021
DOI: 10.1038/s41419-021-04380-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial transcriptomics reveals gene expression characteristics in invasive micropapillary carcinoma of the breast

Abstract: Invasive micropapillary carcinoma (IMPC) is a special histological subtype of breast cancer, featured with extremely high rates of lymphovascular invasion and lymph node metastasis. Based on a previous series of studies, our team proposed the hypothesis of “clustered metastasis of IMPC tumor cells”. However, the transcriptomics characteristics underlying its metastasis are unknown, especially in spatial transcriptomics (ST). In this paper, we perform ST sequencing on four freshly frozen IMPC samples. We draw t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…The intratumoral heterogeneity (ITH) patterns of the paired components in each sample were quantified to estimate the component’s genetic correlations. As expected, the MPP component had higher ITH levels compared with those of the non-MPP component, consistent with the aggressive profile of the MPP component, suggesting an expansionary predominance of this component in early progression [ 19 , 20 ] ( Figure 1 I), as reported previously [ 21 , 22 ]. These results suggest that, although there is some homology between MPP and non-MPP components, both emerged and retained their respective adaptive mutations during their development, with a more complex genomic landscape in the MPP region relative to the other components.…”
Section: Resultssupporting
confidence: 89%
“…The intratumoral heterogeneity (ITH) patterns of the paired components in each sample were quantified to estimate the component’s genetic correlations. As expected, the MPP component had higher ITH levels compared with those of the non-MPP component, consistent with the aggressive profile of the MPP component, suggesting an expansionary predominance of this component in early progression [ 19 , 20 ] ( Figure 1 I), as reported previously [ 21 , 22 ]. These results suggest that, although there is some homology between MPP and non-MPP components, both emerged and retained their respective adaptive mutations during their development, with a more complex genomic landscape in the MPP region relative to the other components.…”
Section: Resultssupporting
confidence: 89%
“…Through spot deconvolution and prior cell marker genes, researchers can estimate the cell composition of spots and further divide the ST sections into several spatially different areas i.e., tumor area, tumor leading-edge area and para-tumor area. Several pilot studies have shown ST-based pathological annotations displayed comparable or even higher accuracy than that from pathologists ( 38 , 82 , 110 , 112 , 123 ) ( Table 2 ). Moreover, ST can distinguish cancer subtypes as well ( 108 ).…”
Section: Clinical Application Of Stmentioning
confidence: 99%
“…This indicates that this newly developed technology could help people successfully reveal the unexplored landscape of heterogeneity. Then, it was widely used in other types of tumors, including melanoma 81 , neuroblastoma 82 , gastric cancer 83 , and breast cancer 83 . In the effort of invasive micropapillary carcinoma (IMPC) studies, spatial transcriptomics analysis provides a valuable resource for exploring the inter- and intratumoral heterogeneity of IMPC and identifies a new marker, SREBF1, which facilitates accurate diagnosis and treatment of the disease 83 .…”
Section: Technologies To Explore Tumor Heterogeneitymentioning
confidence: 99%
“…Then, it was widely used in other types of tumors, including melanoma 81 , neuroblastoma 82 , gastric cancer 83 , and breast cancer 83 . In the effort of invasive micropapillary carcinoma (IMPC) studies, spatial transcriptomics analysis provides a valuable resource for exploring the inter- and intratumoral heterogeneity of IMPC and identifies a new marker, SREBF1, which facilitates accurate diagnosis and treatment of the disease 83 . The spatial heterogeneity analysis-guided treatment decision approach has also been further validated in other types of tumors 84 , 85 .…”
Section: Technologies To Explore Tumor Heterogeneitymentioning
confidence: 99%